2021
DOI: 10.9789/2175-5361.rpcfo.v13.10443
|View full text |Cite
|
Sign up to set email alerts
|

Family violence against children: approach to nursing through genogram and ecomapa / Violência familiar contra criança: abordagem de enfermagem através do genograma e ecomapa

Abstract: Objetivos: descrever a organização familiar frente ao caso de violência contra a criança e analisar através da utilização do genograma e ecomapao risco de familiares em situação de violência. Método: estudo descritivo, tipo estudo de caso realizado no setor pediátrico de um Hospital Municipal da Baixada Litorânea do estado do Rio de Janeiro. Aplicado o Modelo de Calgary de avaliação de famílias. Resultados: através do genograma e ecomapa identificou-se a organização familiar, as relações familiares e as várias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Most studies reported a qualitative study design (n � 58) [17,18,21,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] and , followed by mixed methods (n � 9) [95][96][97][98][99][100][101][102][103] and quantitative designs (n � 3) [22,104,105]. Data collection methods consisted of semistructured interviews alone (n � 36) [17, 41-44, 46, 48, 52, 53, 56, 58, 59, 61-65, 67, 69, 70, 72, 76, 78-81, 83-85, 88, 89, 92, 93, 104] or interviews combined with focus groups [77,98], surveys [22,95,96,[99][100][101][102][103], participant observations [49,51,…”
Section: Study Design and Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies reported a qualitative study design (n � 58) [17,18,21,[41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] and , followed by mixed methods (n � 9) [95][96][97][98][99][100][101][102][103] and quantitative designs (n � 3) [22,104,105]. Data collection methods consisted of semistructured interviews alone (n � 36) [17, 41-44, 46, 48, 52, 53, 56, 58, 59, 61-65, 67, 69, 70, 72, 76, 78-81, 83-85, 88, 89, 92, 93, 104] or interviews combined with focus groups [77,98], surveys [22,95,96,[99][100][101][102][103], participant observations [49,51,…”
Section: Study Design and Methodsmentioning
confidence: 99%
“…Data collection methods consisted of semistructured interviews alone (n � 36) [17, 41-44, 46, 48, 52, 53, 56, 58, 59, 61-65, 67, 69, 70, 72, 76, 78-81, 83-85, 88, 89, 92, 93, 104] or interviews combined with focus groups [77,98], surveys [22,95,96,[99][100][101][102][103], participant observations [49,51,54,55,57,60,66,68,71,73,97], document analysis (i.e., feld notes and medical records) [50,54,66,74,86,96,101], and photographs (i.e., photovoice) [86,90]. Several studies used only focus groups [18,91], analysis of institutional medical records [47], questionnaires [105], and participant observation methods [94]. Te data collection method applied in three studies was not reported [45,82,87].…”
Section: Study Design and Methodsmentioning
confidence: 99%
See 3 more Smart Citations